Paroxysmal Hemicrania - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The clinical characteristics of paroxysmal hemicrania (PH) are reported in a series of 31 patients, ages 5-68 years (mean age 37), identified and followed prospectively at the National Hospital and the Hospital for Sick Children, Great Ormond Street, London, UK from May 1995 to January 2007.